The Effect of Emotional Intelligence and Social Intelligence on Employee Performance of Vivo Mobile Product Consultants in Bengkulu Cityngkulu - David Gunander; Ade Tiara Yulunda (PT. MEMIKATTA PUBLISHER INDONESIA, 2024)
This study aims to determine the effect of emotional intelligence and social intelligence on the performance of Vivo product consultants in Bengkulu. Respondents of this study were permanent employees who worked as product consultants for Vivo mobile phones totaling 44 employees. The sampling technique used in this study was purposive sampling. Data analysis techniques using multiple linear regression analysis, coefficient of determination and hypothesis testing.Furthermore, emotional intelligence and social intelligence simultaneously or together have a significant effect on the performance of Vivo mobile product consultants employees in Bengkulu with a probability value (sig) of 0.000 <0.05. As well as emotional intelligence and social intelligence partially or individually affect the performance of Vivo mobile phone product consultants employees in Bengkulu with a probability value (sig) of each variable emotional intelligence with a probability value (sig) of 0.004 <0.050 has a significant effect on employee performance. And social intelligence with a probability value (sig) of 0.007 <0.05 has a significant effect on employee performance.